WHEAT HERBAGE AMENDMENTS ALTER EMERGENCE DYNAMICS, SEEDLING GROWTH OF LAMBSQUARTER AND SOIL PROPERTIES - ASLAM,F. (2015)
ABSTRACT Crop allelopathy is a potential tool for weed management but allelopathic potential often varies among cultivars and developmental stages of crop. Bioassays were conducted to appraise the allelopathic potential of herbage (incorporated at 8 g kg-1 soil) of different hexaploid wheat (Triticum aestivum) cultivars (Millat-2011, AARI-2011, Lasani-2008 and Faisalabad-2008) collected at different crop growth stages [tillering (Z-30), anthesis (Z-60) and maturity (Z-90)] against lambsquarter (Chenopodium album). Mean emergence time taken by lambsquarter was prolonged over control by anthesis and maturity stage herbage of all wheat cultivars. Final emergence percentage was dropped by 3-17% in response to different growth stages of herbage collection. Maximum suppression in shoot (45 and 78%) and root (60 and 90%) length, and seedling dry biomass (65 and 96%) of lambsquarter over control was recorded under the amendment of anthesis and maturity stages herbage of wheat cultivars. Total chlorophyll contents declined in response to herbage collected at anthesis and maturity stage of all wheat cultivars over control. Phenolic contents on the other hand were increased. Activities of enzymatic antioxidants also varied among all wheat cultivars, and declined by the incorporation of tillering, anthesis and maturity stage herbage. Wheat herbage induced lipid peroxidation in lambsquarter seedling and higher malondialdehyde content (0.56 and 0.77 nmol g-1 FW) was observed by the incorporation of wheat cultivars herbage collected at anthesis and maturity stage, respectively. Anthesis and maturity stage herbage of wheat cultivars Millat-2011, AARI-2011 and Lasani-2008 was more phytotoxic than Faisalabad-2008. Moreover, tillering stage herbage of all wheat cultivars had less inhibitory potential against emergence, seedling growth and biochemical attributes of lambsquarter. Wheat herbage amendment increased the soil pH, phenolic, organic carbon and nitrogen contents as compared to control.